Causal relationships between integrative motivation, self-efficacy, strategy use and English language achievement - Khodadad, Masoomeh; Jagdish Kaur (Penerbit Universiti Kebangsaan Malaysia, 2016)
Due to students' poor level of English achievement in Iran and the fact that some language institutes attribute this problem to students' lack of motivation, this study aimed to investigate the effect of motivation on students' English achievement. In this research motivation is considered in relation to certain individual difference variables which may have important effects on motivation and L2 learning but no attention has been given to them in Iranian English learning context. Hence, this study intended to investigate the causal interrelations between the variables namely, attitudes toward the learning situation, integrativeness, motivation, strategy use, self-efficacy, and English language achievement. To this end, an adapted form of Gardner's (2001a) socioeducational model of second/foreign language learning was used. Research participants were 240 intermediate EFL learners at the Iran Language Institute. The participants were administered the Attitude Motivation Test Battery [AMTB], the Self-Efficacy Questionnaire [SEQ], and the Strategy Inventory for Language Learning [SILL]. Results yielded by Structural Equation Modeling showed that motivation had a direct significant influence on English achievement. However, the effect of motivation on English achievement was stronger when it was affected by attitudes toward the learning situation, integrativeness, and self-efficacy. Thus, to improve students' English achievement in Iranian EFL context, it is necessary to consider not only motivation but also self-efficacy and attitudes, on which students' motivation depend.